The Influence Of Word Of Mouth And Online Reviews On Consumers' Purchase Intention Of Skintific Products On Tiktok Shop With Delivery Speed As An Intervening Variable (A Study On Students Of Universitas Muhammadiyah Pontianak) - Enjelma, Novita; Triana M, Neni (UNIVERSITAS PAKUAN, 2024)
This study aims to identify the influence of Word of Mouth on the Purchase Intention of SKINTIFIC products among female students at Universitas Muhammadiyah Pontianak through Delivery Speed. The research employs an associative method, with a total of 100 respondents who have previously purchased SKINTIFIC products online via TikTok Shop. The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS 3.0 software. Based on the hypothesis testing results, Word of Mouth and Online Reviews directly have a positive and significant influence on Delivery Speed. Other hypotheses indicate that Delivery Speed and Online Reviews directly influence Purchase Intention, whereas Word of Mouth does not have a direct influence on Purchase Intention. Furthermore, based on indirect hypothesis testing, both Word of Mouth and Online Reviews influence Purchase Intention, mediated by Delivery Speed.